PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP EARNING PER SHARE (EPS) PADA PERUSAHAAN YANG MASUK DALAM KATEGORI LQ-45 PERIODE AGUSTUS 2014 – JANUARI 2015 - B41111107, Alifah Nurrahmani Putri (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This research aims to examine the effect of Corporate Social Responsibility (CSR) Disclosure to the company’s Earning Per Share (EPS). This research uses indicator that also used by Sembiring (2005) for measuring Corporate Social Responsibility Disclosure that contains seven categories, such as environment, energy, labor safety and health, other labors, product, society involvement, and general. The population in this research are all of companies listed on the Indonesia Stock Exchange (BEI) and the samples of this research are the company that listed in LQ-45 category in August 2014 – January 2015. Total sample in this research are 44 companies that selected with purposive sampling. Data collection is conducted by collecting secondary data from annual report or sustainability report issued by the company every year. The result of this research indicates that Corporate Social Responsibility (CSR) Disclosure does not have a significant effect to company’s Earning Per Share (EPS). Keywords: Corporate Social Responsibility, Earning Per Share, Annual report, Sustainability report, LQ-45.